1996
DOI: 10.1002/jlac.199619961220
|View full text |Cite
|
Sign up to set email alerts
|

The Configuration of (+)‐8‐Ethylnorlobelol‐I; a Correction of the Literature

Abstract: The piperidine alkaloid (+)-8-ethylnorlobelo-I is assigned the revised 2S,8S absolute configuration as depicted in 7. LiAl(O-tBu)3H reduction of the ketone rac-5 proceeded with a high stereoselectivity to give, after hydrolysis of the carbamate function, the s y n amino alcohol rac-6. Inversion of the C-8 configuration of ent-6 yielded (-)-8-ethylnorlobelol-I ent-7. A short nitrone-alkene-based synthesis of rac-7 has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Both the melting point (mp 88−89 °C) and the specific rotation {[α] D +25.8° (EtOH)} are almost identical with those reported (vide supra) . It is thus concluded that the absolute configuration of natural (+)-8-ethylnorlobelol-I is 2 S -(2 S ) …”
Section: Resultssupporting
confidence: 75%
“…Both the melting point (mp 88−89 °C) and the specific rotation {[α] D +25.8° (EtOH)} are almost identical with those reported (vide supra) . It is thus concluded that the absolute configuration of natural (+)-8-ethylnorlobelol-I is 2 S -(2 S ) …”
Section: Resultssupporting
confidence: 75%
“…Thus, for many years, the absolute configuration was accepted as that described by Schöpf. Recently, Hootelé et al 30 questioned this assignment and correctly revised the absolute configuration to (2S,8S). This assertion of Hootelé was confirmed, a short time later, by Takahata's group, 31 with the first asymmetric total synthesis of (C)-20.…”
Section: Chemistry Of Lobelia Alkaloidsmentioning
confidence: 99%
“…(+)-Allosedridine, 9,10 (-)-8-epi-8-ethylnorlobelol I (4), and (-)-8-epihalosaline (7) were also isolated from A. aspera. As the homologue derivatives 4 and 7 were difficult to separate, their mixture was treated with methyl chloroformate, and the two corresponding carbamates were obtained as pure compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Andrachcinine (1): oil, [R] 22 D -108°(c 2.5, CHCl 3 ); IR (CHCl 3 ) ν max 3335, 1715 cm -1 ; 1 H NMR (CDCl 3 , 250 MHz) δ 5.78 (1H, m, H-4), 5.61 (1H, m, H-3), 3.79 (1H, m, H-8), 3.56 (1H, m, H-2eq), 3.14 (1H, tt, J ) 11, 3.5 Hz, H-6ax), 2.59 and 2.81 (2H, 2 dd, J ) 16, 7 Hz, CH 2 -CO), 2.43 and 2.46 (2H, 2m, CH 2 -CO), 2.31 (3H, s, N-CH 3 ), 1.95 (1H, m, H-5), 1.28-1.75 (8H, m), 1.06 (3H, t, J ) 7 Hz, CH 3 ), 0.92 (3H, t, J ) 7 Hz, CH 3 ); 13 (7), 212 (8) 5) from (-)-8-Epihalosaline (7). Andrachcinidine (5) was obtained from (-)-8-epihalosaline by the procedure described for the synthesis of related compounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation